Perception of corruption across gender, religion, and socioeconomic status - Saha, Asoke Kumar; Dogra, Atanu Kumar; Bairagi, Arunavo; Singh, Vijay Pratap; Hossain, Md. Alamgir; Pata, Sayma Akter (Humanitas: Indonesian Psychological Journal, 2023)
Corruption is a critical issue for Bangladesh, including corruption in higher education. The present study explored the perception of corruption based on gender, religion, and socioeconomic status with factorial survey research design. One hundred twenty participants were selected by purposive sampling technique from male and female university students aged 20-26 years. All the participants were studying in public and private universities. Personal Information Form (PIF) and Perception of Corruption Scale (PCS) were used for this study. The PCS measured the respondents’ level of perception about corruption consisting of 18 items. One-way analysis of variance and t-test were applied to analyze the data. The result indicates no significant difference in perception of corruption based on gender. In contrast, there is a significant difference in the perception of corruption based on religion, with the Hindus having the lowest perception of corruption. Moreover, there is a significant difference in perception of corruption based on socioeconomic status. Therefore, university students’ perceptions of different corrupt practices need to be addressed.